The Effects of Parental Divorce on Children's Self-Confidence and Independence - Safira, Rizqiya; Rozatul Jannah (Socrates: Journal of Education, Philosophy and Psychology, 2025)
Divorce is a social phenomenon with the potential to significantly impact children's psychological development, particularly in terms of self-confidence and independence. This article aims to explore the influence of divorce on these two aspects through a literature review. By examining various studies and relevant sources, it is evident that divorce can affect children both directly and indirectly, depending on factors such as the child's age, family support, and the parents' conflict management strategies. Common impacts include decreased self-confidence, difficulty in decision-making, and limitations in social and emotional independence. However, family support and a nurturing environment can serve as mitigating factors, helping children overcome these negative effects. This study is intended to provide insights into children's needs in post-divorce situations and offer recommendations for parents and policymakers to support children's optimal development.